Biodamages and protection of leather and fur - Pekhtasheva, Elena; Neverov, Anatoly; Zaikov, Gennady (Publishing House of Lviv Polytechnic National University, 2012)
The paper presents the information about biodamages and protection of leather and fur. The contributors put a special emphasis on rawhide microflora, putrefied hide microflora, effect of prior operations on bioresistance of leather, interesting facts, fur skin structure and properties changes by microorganisms and the methods of leather preservation against microorganism impact. Приведено дані стосовно біопошкодження і захисту шкіри та хутра. Особливу увагу приділено мікрофлорі сирої шкіри, процесу біорозкладу натуральної шкіри, впливу мікроорганізмів на різних стадіях вичинки шкіри, змінi структури шкіри і хутра під впливом мікроорганізмів та методам захисту натуральної шкіри.
Біопошкодження та захист шкіри і хутра
Keywords: biodamage; fur; protection; leather; bioresistance; біопошкодження; захист; хутро; шкіра; біологічний опір